Analysis of the Potential of Creative Marketing Strategies in Increasing Sales in the ANURATU Convection Industry - Fahrudin, Fahrudin; Shofi, Ahmad; Masyhur, Ahmad; Qodir, Abdul; Iman, M. Kamilul (Perpustakaan dan Penerbitan Unismuh Makassar, 2024)
This study analyzes the potential of creative marketing strategies to enhance sales in the ANURATU convection industry. The research aims to explore the deeper potential and future opportunities of this industry, contributing to the relatively under-researched area of creative marketing. By identifying and understanding the unique factors that drive consumer interest and engagement, this study seeks to provide valuable insights for businesses looking to innovate and grow in a competitive market. The study employs a qualitative approach, utilizing descriptive methods to gather and present data based on observations and interviews. ANURATU, a small-scale home-based business, produces high-quality vintage-themed apparel. Despite using manual production processes and simple equipment, ANURATU has successfully marketed its products both domestically and internationally, including in regions such as Sumatra, Bali, and Singapore. The research highlights the role of digital marketing as a powerful tool for increasing visibility and attracting a wider customer base. Additionally, product diversification has proven to be an effective strategy in appealing to different consumer segments, expanding the brand's reach. The findings suggest that creative marketing strategies, such as leveraging social media platforms, influencer collaborations, and limited-edition collections, are essential for boosting sales and fostering customer loyalty. With a focus on quality and trust, ANURATU has the potential for significant growth and sustainability. The study concludes that by continuing to embrace creative marketing techniques, ANURATU can establish itself as a leading brand in the vintage apparel industry.